Regional input-output matrices, an application to manufacturing exports in Mexico - Daniel Chiquiar; Jorge Alvarado; Miroslava Quiroga; Leonardo Torre (Banco de México, 2017)
Based on the national Input-Output Matrix (IOM) 2012 calculated by INEGI, we use Flegg's approach to estimate four regional Input-Output Matrices (RIOMs) using Banco de México's regionalization (Northern, North-Central, Central and Southern). The RIOMs are employed to evaluate the impact on regional gross output, value added and employment resulting from a 10,000 million dollar shock on Mexican manufacturing exports. The results show that the effects on the absolute values of gross output, value added and employment in the North are clearly larger than those estimated for the other regions. Another finding is that the total effects of the regional shocks tend to concentrate in the manufacturing sector, with the highest concentration observed in the North, and the lowest in the South. We also find that indirect effects of these shocks tend to be larger in regions far from the US border.
Keywords: R11; R12; R15; 330; Input-Output Model; Regional Analysis; Multiplier Effects; Exports